Determinants of Share Return in Manufacturing Companies Listed on IDX for the Period of 2019-2021 - Dede Hertina; Irmayani Wardani (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Interest in investing, especially in stocks in the Indonesian capital market, is getting higher, so it is important to analyze the factors that can affect the level of stock returns in order to minimize the risks that will be faced. This study aims to determine the condition of the company's financial performance, capital structure, and stock returns and examine the effect of the company's financial performance and capital structure on stock returns in companies in the manufacturing sector listed on the Indonesia Stock Exchange for the period 2019–2021. The research method used is descriptive and verified. The population in this study is made up of manufacturing sector companies listed on the Indonesia Stock Exchange for the period 2019 to 2021. The sampling technique uses purposive sampling in order to obtain 124 companies to be studied. Data Analysis Using Panel Data Regression. The company's fluctuating financial performance tends to decrease, as seen from the average value of EPS, ROA, and ROE. The capital structure used is dominated by debt. The company's financial performance, represented by ROA and ROE, has an effect on stock returns, but the company's performance, represented by EPS, has no effect on stock returns. The capital structure represented by DER has an effect on stock returns. Research implication – The theoretical contribution of the